NURSING CARE: THE FAMILY AND THE CHILD WITH ONCOLOGICAL PAIN - Grassele Denardini Diefenbach; Maria da Graça Corso Motta (Universidade Federal do Paraná, 2012)
This study aimed to investigate the functioning of the nursing team in the care for children with oncological pain in the hospital environment, from the standpoint of the family. It is an exploratory, descriptive study with a qualitative approach, undertaken in the Pediatric Hematology and Oncology Center of a large hospital in the capital of Rio Grande do Sul, Brazil, between May and June 2010. Nine families participated in the study; the Creative-Sensitive Method was used for the collection of data, through dynamics of creativity and sensitivity, which was analyzed through the framework of Thematic analysis. It was determined that the pain resists definition, constantly terrorizing the child, who is soothed in her 'safe haven' - the family. Such circumstances open avenues for the role of nursing, as they lead to the deepening of knowledge of knowing and doing in Nursing, making it possible to visualize and interpret the different realities of the child with oncological pain and their family.